Intra-Party Crisis in Nigeria: A Study of the 2022 All Progressives Congress Primaries in Abia Central Senatorial Zone - Ndubuisi, Uchechukwu; Uduma, Dick O. (Kashere Journal of Politics and International Relations, 2025)
This study focused on intra-party crisis in Nigeria with emphasis on the 2022 All Progressive Congress (APC) primaries for Abia Central Senatorial Zone. The increasing cases of intra-party crisis in Nigeria have remained a threat to the sustenance of democracy. Two hypotheses were evaluated and the study relied on the Structural Functionalist theory as a framework of analysis. The study used secondary data and adopted a survey research design, using questionnaires as an instrument of data collection. Data was collected from the sample size of 244 All Progressives Congress (APC) members randomly chosen from the population of 624 All Progressives Congress (APC) executives from the 52 wards in Abia Central Senatorial Zone. Responses were presented in tables and hypotheses were tested using a 5-point Likert scale. The findings revealed that intra-party crises have a significant effect on the performance of political parties in elections and poor implementation of the party constitution and Electoral Act are all enablers of intra-party crises in Nigeria political parties. The study concludes that political parties remain an important institution for any democracy to succeed and the continuous cases of intra-party crises have constrained political parties to contribute towards the consolidation of democracy in Nigeria. Thus, if Nigeria’s political parties must help deepen Nigeria’s democracy, internal party democracy should be promoted, issues leading to factionalization addressed and the dictates of the party constitution and Electoral Act should not be compromised.